Dialektika Living Qur’an dalam Manajemen Pengelolaan Zakat Pada Baznas (Bazis) DKI Jakarta - Yasdar, Yasdar; Zulki, Ahmad (Al-Mizan (e-Journal), 2024)
This article aims to analyze the dialectics of living Qur'an in the management of zakat at the National Amil Zakat Agency (Baznas) or Zakat Infaq dan Shadaqah Agency (Bazis) Special Capital Region (DKI) Jakarta. This research is field research with a living Qur’an approach and is analyzed descriptively and qualitatively. The results show that the dialectic of living Qur'an produces a comprehensive solution by presenting a re-reading of zakat management that is adjusted to contemporary zakat management. The dialectic of living qur'an in zakat management at Baznas (Bazis) DKI Jakarta is carried out in various forms and models consisting of comprehensive management including poverty reduction, evaluation and relevance and transformation of zakat management which includes comprehensive-contemporary management, digitalization of zakat, diversification of programs and living qur'an-based zakat management solutions.